Umbilical cord separation time: chlorhexidine vs methylated-spirit (2019)
Background: Use of topical antiseptics could reduce the incidence of infection; however, studies have suggested that some antiseptics prolong the time for cord separation when compared with others. Aims To compare the umbilical cord separation time between neonates receiving 7.1% chlorhexidine gel and methylated spirit. Methods: A quasi-experimental research design was employed for this study. A multistage sampling technique was used to select three primary health centers in Ibadan, Nigeria. A total of 212 newborns (118 newborns in the chlorhexidine group and 94 in the methylated spirit group) were enrolled into the study. Findings: There was a statistically significant difference in mean time to cord separation between chlorhexidine (9.53 ± 4.559 days) and methylated-spirit group (7.98 ± 2.984) (t=2.840; P=0.005). Conclusions: Chlorhexidine gel prolongs cord separation when compared to methylated spirit. Prolonged cord separation time was the major cause of dissatisfaction in the two study groups. The increased cord separation time associated with chlorhexidine should not eliminate it in settings where the risk of cord infection is high, but mothers should be informed of this.